Internal vs. international migration: Impacts of remittances on child well-being in Vietnam - Michele Binci; Gianna Claudia Giannelli (Institute for the Study of Labor (IZA), 2012)
This paper focuses on the effects of domestic and international remittances on children's well-being. Using data from the 1992/93 and 1997/98 Vietnam Living Standards Surveys, we investigate average school attendance and child labour in remittance recipient and non-recipient households. The results of our cross-section and panel analyses indicate that remittances increase schooling and reduce child labour. Although international remittances are found to have a stronger beneficial impact than domestic remittances in the cross-section analysis, the panel analysis reverses this result, showing that the only significant impact stems from domestic remittances.
urn:nbn:de:101:1-2012081412480
Keywords: F22; I39; J13; O15; 330; migration; remittances; schooling; child labour; panel data; Vietnam; Rücküberweisung (Migranten); Kinder; Schulbesuch; Kinderarbeit; Schätzung; Vietnam